The Influence of Organizational Citizenship Behavior and Competence on Performance Achievement - Bisowarno, Bandot; Qomariah, Nurul; Sanosra, Abadi (Budapest International Research and Critics University, 2024)
Every government agency is interested in the best performance that can be produced by the series of systems that apply in the organization. Human resource management is one of the key factors to get the best performance. This study aims to determine the effect of organizational citizenship behavior (OCB) and competence on employee performance. This study is a type of comparative causal research. The data used in this study are primary data. The population in this study were employees at the Jember Regency Health Office who have the status of State Civil Apparatus (ASN and PPPK) including employees of the Health Center and UPTD as many as 1,531 people. The sample was determined by the slovin formula as many as 100 respondents. Descriptive analysis, validity test and reliability test as well as direct influence test were carried out to support the research conducted. The results of the study stated that organizational citizenship behavior (OCB) and competence have a positive and significant effect on employee performance at the Jember Regency Health Office.